Answering Contemporary Problems With The Wasatiyah Fiqh Approach: A Study Of Ai, Crypto, Online Games - Julianto, Tedy; Niffilayani, Anita; Fitri Wahyuni , Marina (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
The rapid development of digital technology has generated various contemporary issues in Islamic jurisprudence that require adaptive and relevant legal responses. Phenomena such as Artificial Intelligence (AI), crypto assets, and online gaming present new challenges in the areas of religious authority, economic transactions, and digital entertainment ethics. This article aims to analyze these issues through the perspective of moderate fiqh, which emphasizes contextual interpretation and public benefit (maslahah). This study employs a library research method with a qualitative-descriptive approach, examining contemporary fiqh literature, fatwas issued by Islamic institutions, and relevant scholarly journal articles concerning AI, crypto assets, and online gaming. The findings reveal that the legal status of these three phenomena cannot be determined in an absolute manner; rather, it must be assessed based on the purpose of use, potential benefits, possible harms, and its conformity with the principles of maqasid al-shari‘ah. AI may be utilized as a supportive tool within ethical boundaries, crypto assets require evaluation based on transparency and functional utility, while online gaming is permissible as long as it does not involve elements of gharar, maysir, or negligence of religious obligations. This study concludes that moderate fiqh offers a flexible, contextual, and responsive legal framework for addressing contemporary issues in the digital era.